2020
DOI: 10.1002/jpen.1863
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Energy and Protein Requirements in Relation to Nitrogen Kinetics, Nutrition, and Clinical Outcomes in Infants Receiving Early Enteral Nutrition Following Cardiopulmonary Bypass

Abstract: Background Nutrition therapies in children with congenital heart disease (CHD) after cardiopulmonary bypass (CPB) is crucial, but energy and protein requirements remain undefined. We assessed energy and protein requirements, with nitrogen kinetics and clinical outcomes, in infants with complex CHD following CPB. Methods Infants were randomized to control (1.3 g/kg/d), moderate protein (MP, 2.5 g/kg/d), or high protein (HP, 4 g/kg/d) groups. Resting energy expenditure (REE) was measured 6 hours post‐CPB and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
(147 reference statements)
0
21
0
2
Order By: Relevance
“…Increasing the quality and quantity of dietary nutrients, and focusing on nutrient energy-dense feed, are associated with improved weight gain and the achievement of nutritional targets [ 1 , 2 ]. Total fluid intake in conjunction with optimal energy protein supply, guided by a multidisciplinary team is essential [ 50 , 51 ].…”
Section: Pre- and Post-operative Strategies And Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the quality and quantity of dietary nutrients, and focusing on nutrient energy-dense feed, are associated with improved weight gain and the achievement of nutritional targets [ 1 , 2 ]. Total fluid intake in conjunction with optimal energy protein supply, guided by a multidisciplinary team is essential [ 50 , 51 ].…”
Section: Pre- and Post-operative Strategies And Recommendationsmentioning
confidence: 99%
“…A primary aim in infants with CHD is also to provide sufficient dietary protein to enable adequate new protein synthesis. Proteins are necessary for tissue repair and growth, and they facilitate wound healing, modulate inflammatory responses, and preserve skeletal muscle mass [ 8 , 51 ].…”
Section: Pre- and Post-operative Strategies And Recommendationsmentioning
confidence: 99%
“…An imbalance between energy intake and requirements leads to malnutrition among these infants postoperatively. It has been well documented that the energy intake of infants with congenital cardiac repair is less than their requirements because of fluid restrictions, feeding intolerance, and frequent feeding interruptions 2–5 . Breast milk is considered as the ideal nutrition that provides several benefits to the infants 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have shown that the supplementation of expressed breast milk (EBM) or energy‐dense formula feeds via tube feeding (nasogastric/orogastric) in the immediate postoperative period increases the energy or protein intakes postoperatively 11,12 . Thus supplemented feeding improves weight as compared with those fed with EBM or standard formula feed 4,11,12 . One randomized controlled trial (RCT) has reported that feeding interruption and feeding intolerance are the major problems that hinder energy consumption, even in supplemented group of patients 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation